Kelainan Genetik Pada Down Syndrome - Cahyana, Adinda Husna; Syachrani , Fayza; Maharani , Mentari Putri; Himayani, Rani; Rahmanisa, Soraya (CV. Jasa Sukses Abadi, 2025)
Down syndrome (SD) is a common and easily recognized genetic disorder. In the genetic disorder trisomy or SD, there is an extra chromosome on chromosome 21. This chromosome causes the production of certain proteins in excessive amounts, thus disrupting the normal growth of the organism and causing changes in brain development. The estimated incidence of SD is one in 800-1000 births. The incidence of SD in the world is 10 per 10,000 live births, and in recent years this figure has increased. The World Health Organization (WHO) estimates that there are around 8 million SD sufferers worldwide. In Indonesia itself, the prevalence of SD is 1 per 600 live births. Down syndrome is a condition where the sufferer has retarded physical and mental development due to abnormal chromosome development. Chromosomes contain genetic material that determines human characteristics, so that some children with Down syndrome will usually experience mental disabilities, whether mild or moderate.